Tracey Rowland, Catholic Theology, London–New York 2017, ss. 260. - Raczyński-Rożek, Maciej (Teologia w Polsce, 2020)
Recenzja książki: Tracey Rowland, Catholic Theology, London–New York 2017, ss. 260.